2017
DOI: 10.1371/journal.pone.0188704
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the diagnostic validities of Xpert MTB/RIF and interferon-γ release assays for tuberculous pericarditis using pericardial tissue

Abstract: BackgroundThis study aimed to assess the diagnostic performance of Xpert MTB/RIF for tuberculous pericarditis (TBP) using pericardial tissues.MethodsThe study involved 30 patients admitted with suspected TBP from January–December 2016; three patients were later excluded. The interferon-γ release assay (T-SPOT.TB) and the Xpert MTB/RIF test were performed using peripheral blood and pericardial tissues, respectively. TBP was confirmed using pericardial histopathology and a composite reference standard (CRS). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Diagnostic values of t-Spot.tB. In TBP patients, the frequency of SFCs was 229 per million PEMC (IQR, 86-492), which was significantly higher than in non-TB patients (14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , P < 0.001). Evaluation of the efficiency of the T-SPOT.TB assay (cut-off point in current clinical use: 6 or more spots and twice the number of spots than the negative control well) showed that it had sensitivity, specificity, PPV, NPV, PLR, NLR, and DOR values of 92.3%, 87.9%, 81.8%, 95.1%, 7.6, 0.088, and 87.0, respectively (Table 2).…”
Section: Results Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic values of t-Spot.tB. In TBP patients, the frequency of SFCs was 229 per million PEMC (IQR, 86-492), which was significantly higher than in non-TB patients (14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , P < 0.001). Evaluation of the efficiency of the T-SPOT.TB assay (cut-off point in current clinical use: 6 or more spots and twice the number of spots than the negative control well) showed that it had sensitivity, specificity, PPV, NPV, PLR, NLR, and DOR values of 92.3%, 87.9%, 81.8%, 95.1%, 7.6, 0.088, and 87.0, respectively (Table 2).…”
Section: Results Clinical Characteristicsmentioning
confidence: 99%
“…The reported positive rate of conventional MTB culture on PF was only 53%, and the sensitivity of pericardial biopsy varied from 10 to 64% 5 . In addition, pericardial biopsy was invasive, and the histopathological results were influenced by the location of the biopsy site, the quality of equipment, and the experience of physicians 14 . Thus, the number of false-positive cases might be overestimated when diagnostic tests are evaluated against culture or histopathology, leading to underestimation of specificity.…”
Section: Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 showed the flowchart of the research collection, while Table 1 provided a summary of the included studies. Of the nine studies included, three were carried out in Pakistan 10 , 13 , 15 , two were conducted in South Africa 12 , 14 , and the rest were carried out in Turkey 17 , Iran 9 , China 16 , and Spain 11 . All studies used a prospective observational design.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the risk of bias in the subject preference area, six studies 9 , 10 , 12 , 14 , 16 , 17 were labeled as low risk, two studies 13 , 15 were labeled as high risk, and one study 11 was labeled as an unclear risk because it did not explain the exclusion criteria clearly. The reason for the high risk of bias in this domain was due to inappropriate exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%